2019
DOI: 10.1177/0269216318818011
|View full text |Cite
|
Sign up to set email alerts
|

Brief psychosocial interventions improve quality of life of patients receiving palliative care: A systematic review and meta-analysis

Abstract: Background: Patients with a terminal disease report a high need for psychosocial and spiritual support. Previous literature reviews on psychosocial interventions in palliative care were restricted to certain subtypes of techniques, included a wide range of patients, conditions, and settings, or required a number of sessions unrealistic to be achieved in patients nearing the end of their lives. Aim: The aim of this study was to review and synthesize the evidence on brief psychosocial interventions (i.e. four se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 74 publications
(193 reference statements)
0
53
0
3
Order By: Relevance
“…The general goal is to relieve symptom distress and to improve quality of life of patients in various stages of an oncological disease. Particularly in advanced cancer populations and palliative care, music therapy has recently received high attention in both research and clinical care (Stützlinger et al, 2018;Warth et al, 2019a). The use of music and sounds to affect human spirit and to heal dates back to ancient times.…”
Section: Introductionmentioning
confidence: 99%
“…The general goal is to relieve symptom distress and to improve quality of life of patients in various stages of an oncological disease. Particularly in advanced cancer populations and palliative care, music therapy has recently received high attention in both research and clinical care (Stützlinger et al, 2018;Warth et al, 2019a). The use of music and sounds to affect human spirit and to heal dates back to ancient times.…”
Section: Introductionmentioning
confidence: 99%
“…Psychological symptoms such as anxiety and agitation are highly prevalent in dying patients with COVID-19 [ 6 , 19 ]. Psychosocial interventions in palliative care can relieve emotional and existential distress and improve quality of life [ 36 ]. A rapid review recommended that psychosocial care should be provided as part of the palliative care for patients with COVID-19 [ 33 ], although data in COVID-19 are not yet available [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…[6,17] Psychosocial interventions in palliative care can relieve emotional and existential distress and improve quality of life. [34] Therefore, a rapid review recommended to healthcare professionals providing psychosocial care in palliative care for patients with COVID-19, [31] although data in COVID- 19 are not yet available. [35] Results: Most experts strongly (52.9%) or conditionally (39.7%) recommended that healthcare professionals providing psychosocial care should be part of the treatment team of patients with serious COVID-19 with persistent symptoms and concerns despite optimal disease treatment.…”
Section: Patients With Serious Covid-19 In Palliative Care and Distrementioning
confidence: 99%
“…These measures warrant in-depth assessment in a larger study with adequate statistical power, particularly in light of literature showing improved quality of life and psychosocial and spiritual well-being with patient use of similar brief psychosocial interventions. 7,8,11 A new study is currently underway to further examine these outcomes. 38 Of note, well-being and quality of life in advanced cancer patients can be multi-faceted; 39 therefore, forthcoming studies should include a comprehensive assessment of patient well-being and quality of life without increasing patient burden.…”
Section: Main Findingsmentioning
confidence: 99%
“…10 A recent systematic review on the use of psychosocial and spiritual therapies of short duration (<4 sessions or <21 days), including reminiscence or life review interventions, demonstrated positive effects on patient quality of life, emotional and existential distress in the palliative care context. 11 Reminiscence programmes delivered by care staff and using technology have been demonstrated to improve well-being and quality of life in individuals with dementia in community and inpatient settings. 12,13 However, findings from the dementia patient population may not generalize to the specialist palliative care context as the latter involves individuals with lifethreatening illness nearing the end of life.…”
Section: Introductionmentioning
confidence: 99%